Churches Heating: The Optimum Balance Between Cost Management and Thermal Comfort. (2016) - Turcanu, Florin Emilian; Verdes, Marina; Serbanoiu, Ion
Abstract: In this paper is presented a numerical and cost benefit approach of the indoor climate environment created inside of a historical Roman-Catholic church that will be subjected to restoration in the near future. The heating system used in present is with static heaters. The numerical model has as proposes to subject to comparison another heat system: floor heating and mechanical ventilation system in order to have a better understanding of the differences between them and the economical implication of this changes. Historical buildings and churches constitute a problem because they have enormous volumes and the envelope has a low efficiency. From the economical point of view, the solution must the feasible. The comparative results showed that the existing heating system is inefficient and has a lot of damage for the artworks and the painting inside the church.